Occupational ultraviolet light exposure increases the risk for the development of cutaneous squamous cell carcinoma: a systematic review and meta-analysis - Schmitt, Jochen Maximilian; Seidler, A.; Diepgen, Thomas L.; Bauer, A. (British journal of dermatology, 2011)
Background Despite the fact that ultraviolet (UV) light exposure is the most important risk factor for cutaneous squamous cell carcinoma (SCC) there is an ongoing debate concerning the relationship between cumulative work-related UV exposure and SCC occurrence. Objectives To analyse comprehensively the relationship between work-related UV exposure and SCC risk. Methods We conducted a systematic electronic literature search in PubMed (up to 5 May 2010) supplemented by a hand search, which identified 18 relevant studies that were included in the review. Data abstraction and study quality assessment was done independently by two reviewers. Maximally adjusted odds ratios (ORs) and corresponding 95% confidence intervals (CIs) of all included studies were pooled in a random-effects meta-analysis. Sensitivity analysis included meta-regression on study-specific covariates to explore the robustness of the results and to identify sources of heterogeneity between studies. Eighteen studies (six cohort studies, 12 case-control studies) met the eligibility criteria and were included in the systematic review. Results Sixteen studies (89%) found an increased risk of SCC in individuals with occupational UV light exposure compared with individuals without occupational UV light exposure, reaching statistical significance in 12 studies. Two studies found no association between occupational UV light exposure and SCC occurrence. The pooled OR (95% CI) was 1·77 (1·40-2·22) and did not differ significantly between cohort studies [OR (95% CI): 1·68 (1·08-2·63)] and case-control studies [OR (95% CI): 1·77 (1·37-2·30)]. Meta-regression analyses suggested an increasing strength of the association between occupational UV light exposure and SCC risk with decreasing latitude. Conclusions In summary, there is consistent epidemiological evidence for a positive association between occupational UV light exposure and SCC risk.